Tomato yield enhancement with plasma-activated water as an alternative nitrogen source - Ryza A. Priatama; Hong Kwan Beak; Seungil Park; Ilchan Song; Soon Ju Park; Seong Bong Kim; Young Koung Lee (BMC Plant Biology)
Abstract Background Non-thermal plasma has recently gained popularity in agriculture for their potential applications in precultivation, cultivation, and postharvest processes. Plasma-treated seeds exhibit enhanced plant growth, and their fruits can be stored for extended periods. However, limited research has been conducted to confirm the effects of plasma-activated water (PAW) treatment on plant cultivation from germination to harvest. In this study, we aimed to investigate the use of PAW, generated using a surface dielectric barrier discharge (SDBD) device, for tomato cultivation from germination to harvest. Results PAW irrigation significantly improved seedling development, increasing cotyledon area by up to 4-times and seedling biomass by up to 3.6-times compared to the untreated control. During the reproductive phase, PAW treatment doubled the number of flowers and increased chlorophyll content and leaf area. At harvest, PAW irrigation led to a 3-times increase in fruit number and up to a 3.9-times increase in plant biomass. Moreover, the characteristics of fruits produced by PAW-treated plants were normal. Conclusion These results highlight the potential of PAW in future agricultural practices as an alternative ecofriendly nutrient source for plant irrigation under nutrient-limiting conditions, during all developmental stages.